Management of Proximal Caries That Are Not Clinically Detectable - Muhammad Fachrul Al Ghifari; Fajar Fatriadi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Tooth decay is one of the most common dental diseases. Clinical examination alone is not sufficient to detect carious lesions. Additional diagnostic support, such as radiographic imaging, is necessary to aid in establishing an accurate diagnosis and appropriate treatment plan. Case: A 21-year-old female patient came to the Conservative Dentistry clinic at RSGM Unpad with complaints of a cavity in her lower right molar, and sometimes food gets stuck in it. Additionally, the patient also complained of occasional sensitivity in the tooth when eating or drinking cold items, which quickly subsides. Case Treatment: The treatment for the filling of tooth 46 was completed in four visits. The first visit included taking the patient's history and an initial examination. The second visit involved caries removal, Class I preparation, discovery of a distal-proximal lesion, further Class II preparation, and a trial placement of a sectional matrix. The third visit included the placement of the sectional matrix, Class II composite restoration, and polishing. The fourth visit covered the control of the Class II composite restoration and re-polishing. Discussions: Proximal caries is a type of decay that is difficult to detect clinically. The bitewing radiographic technique is the standard method for detecting proximal caries through the radiolucent image, which indicates the presence of demineralization in the tooth. Conclusion and Suggestions: The importance of clinical examination, along with the supporting examination through bitewing radiography, is to detect proximal caries, thereby preventing errors in determining the treatment plan.